Awareness Regarding Cervical Cancer among Reproductive Age Women Residing in Nuwakot District - Bajracharya, S. L.; Chalise, P. (Kathmandu University Medical Journal, 2021)
Background Cervical cancer is the most common malignancy among Nepalese women and it is main cause of death among reproductive age women in Nepal. Objective The objective of this study was to find out awareness regarding cervical cancer among reproductive age women residing in Nuwakot district. Method A descriptive cross-sectional study was conducted to assess the awareness about cervical cancer among reproductive age women of Nuwakot district from April to May 2021. A total of 190 respondents were interviewed using structured questionnaire. Descriptive and inferential analysis were conducted using SPSS version 23 not licenced but trail version. Result Among 190 reproductive age women, the mean age was 33.37±8.39 (Mean±SD). Nearly 10% of respondents answered the meaning of cervical cancer correctly. Among them 30% of respondents did not know about the cause. Similarly, only 7.4% of respondents answered that HPV Infection was risk factor, 2.6% of respondents knew about appropriate age for HPV vaccine. However, nearly 19% of respondents answered that cervical cancer screening was needed for sexually exposed women. There was a significant difference in mean of awareness among different ethnicity (p=0.014), educational level (p=0.001) and there was no significant difference in mean of awareness among different age group, marital status, occupation, family history of cervical cancer and smoking habit. Conclusion Most of the reproductive age women were unaware about meaning, causes, risk factors and preventive measures of cervical cancer. So, there is a need for the implementation of awareness programs on cervical cancer and its preventive measures in this community.